Third-order optical nonlinearities and fs-laser microfabrication of 3D waveguides in borate glasses doped with rare-earth ions - Santos, Sabrina Nicoleti Carvalho dos (2019)
Technological breakthroughs have allowed the development of lasers capable of generating ultrashort pulses of high intensity. In this direction, femtosecond laser pulses have proven to be an excellent tool for both processing and nonlinearity studies in materials. Vitreous materials, in general, have stood out for presenting interesting nonlinear optical processes, and are promising candidates for the development of photonic devices. Borate glasses, specifically, have been only sparsely investigated concerning nonlinear optics. The addition of rare-earth ions in these glasses has attracted considerable attention due to its multifunctionality for the development of optoelectronic and photonic devices. Considering the importance of this glass as a nonlinear optical material, this work aimed to use femtosecond laser pulses in two main directions: (i) the study of borate glass optical nonlinearities, as well as the analysis of the effect of rare-earth ions on these properties and (ii) the production of threedimensional waveguides using laser processing. These results were obtained using Z-scan techniques and femtosecond laser microfabrication, which allowed nonlinear optical characterization and waveguide production, respectively. Initially, the third-order nonlinear optical properties of B2O3-BaO and B2O3-BaO-SiO2-DyEu glasses were investigated. By modeling the experimental results it was possible to show that oxygen in the vitreous matrix plays a fundamental role in nonlinearities. It was also demonstrated the fabrication of waveguides in the B2O3-BaO-SiO2 sample doped with the Dy3+ and Eu3+ ions, which were able to propagate the fluorescence of the glass by coupling the ultraviolet light. The same procedures were performed on the calcium lithium tetraborate (CaLiBO) system doped with two rare-earth ions, Tb3+ and Yb3+. The results from the nonlinear optical characterization were modeled, revealing that the nonlinearity has a significant contribution associated with the oxygen present in the matrix. However, the electronic molar polarizability evidenced that there is a strong influence of rare-earth ions polarizability in these properties. Thus, it can be inferred that the combination of oxygen and the polarizability of rare-earth ions are responsible for the nonlinearity present in the vitreous system. The fabrication of three-dimensional waveguides in CaLiBO samples showed homogeneity, with single-mode operation at 632.8 nm, 612 nm, 594 nm, 543 nm and 405 nm wavelengths. Summing up, the results presented here are of great importance and expand the knowledge regarding the nonlinear optical characterization and the manufacture of waveguides in rare-earth ion doped borate glasses that are important for the research in the field of photonics.